A new genus and eight new species of tail-wagger snails from eastern South Africa, with a key to genera within Sheldonia s.l. (Gastropoda: Urocyclidae) - Herbert, David G. (European Journal of Taxonomy, 2017)
A new genus and eight new species of urocyclid snails are described from eastern South Africa. The supra-specific taxa Kerkophorus Godwin-Austen, 1912 and Microkerkus Godwin-Austen, 1912 are considered distinct from Sheldonia Ancey, 1887 and are treated as separate genera. The diagnostic morphological features of all three genera are detailed and a fourth genus, for which there is no existing name, is described as new: Selatodryas gen. nov. A provisional key to genus-level taxa within Sheldonia s.l. is provided. Eight species are described as new: Kerkophorus piperatus sp. nov., K. vittarubra sp. nov., K. scrobicolus sp. nov., K. terrestris sp. nov., Microkerkus sibaya sp. nov., Selatodryas roseosoma gen. et sp. nov., S. luteosoma gen. et sp. nov. and Sheldonia fingolandensis sp. nov.